Facing Energy Trilemma with Solar Power Generation as Future Main Player in Infrastructure Development. Issue 1 (November 2020) - Amran, Mohd; Radzi, Mohd
Abstract: Energy trilemma provides huge challenges for policy makers and implementers to reform the energy systems. One of the key efforts is to improve renewable energy (RE) participation, which is not only applicable in infrastructure development of urban areas, but also covering rural areas. Meanwhile, the growth of solar power generation can be seen clearly, and the increased generation could contribute significantly to supply electricity in both urban and rural areas with different challenges. Thus, this paper will address the strategies of facing Energy Trilemma and followed by role of photovoltaic (PV) systems in supplying electricity for urban and rural areas. The works done will be seen important equally in order to finally address full coverage of electricity with stable and reliable systems.